2018
DOI: 10.3390/v10090458
|View full text |Cite
|
Sign up to set email alerts
|

HHV-8 Seroprevalence and Genotype Distribution in Africa, 1998–2017: A Systematic Review

Abstract: Human herpes virus type 8 (HHV-8) is the causative agent of Kaposi’s sarcoma (KS). We systematically reviewed literature published between 1998 and 2017, according to the PRISMA guidelines, to understand the distribution of HHV-8 infection in Africa. More than two-thirds (64%) of studies reported on seroprevalence and 29.3% on genotypes; 9.5% were on both seroprevalence and genotypes. About 45% of African countries had data on HHV-8 seroprevalence exclusively, and more than half (53%) had data on either seropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 111 publications
(145 reference statements)
0
23
0
Order By: Relevance
“…In addition, the African subtype B was detected in North-western Argentina which is consistent with the results obtained by ORF-26 subtype characterization. Moreover, we have reported for the first time the occurrence of the African subtypes A5 and F in Argentina, which had been previously described not only in Africa but also in France, Cuba and Brazil (Lacoste et al, 2000; Kourí et al, 2005; Kourí et al, 2012; Tozetto-Mendoza et al, 2016; Etta et al, 2018). These results highlight the African contribution to the demographic history of the country.…”
Section: Discussionmentioning
confidence: 52%
“…In addition, the African subtype B was detected in North-western Argentina which is consistent with the results obtained by ORF-26 subtype characterization. Moreover, we have reported for the first time the occurrence of the African subtypes A5 and F in Argentina, which had been previously described not only in Africa but also in France, Cuba and Brazil (Lacoste et al, 2000; Kourí et al, 2005; Kourí et al, 2012; Tozetto-Mendoza et al, 2016; Etta et al, 2018). These results highlight the African contribution to the demographic history of the country.…”
Section: Discussionmentioning
confidence: 52%
“…reports that subtype A was detected more frequently among HIV-infected patients with or without KS than HIV-negative subjects 15 . Previous studies have demonstrated the clustering patterns of HHV-8 subtypes with geography and ethnicity, and these may have arisen through ancient human migrations 44 , 47 . In addition, de Oliveira Lopes et al .…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 6 samples were typable, and subtype A5 was the most predominant (50%), followed by B1 variant of subtype B (33%) and a subtype C variant close to C7 (17%). A5 and B subtypes are the most frequent subtypes found in sub-Saharan Africa, with a distribution on the African continent of 42%, 27% and 18% for subtypes B, A5 and C respectively 16 , 43 , 44 . Our results are consistent with Betsem et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although located in a highly endemic area, there is a lack of knowledge on the epidemiology of HHV-8 and KS in Gabon [ 50 , 51 ]. The present work aimed to gain new insights into the epidemiology of HHV-8 and its genetic diversity in this central African country.…”
Section: Introductionmentioning
confidence: 99%